Synthesis and bactericide activity of nanofiltration composite membranes - Cellulose acetate/silver nanoparticles and cellulose acetate/silver ion exchanged zeolites - Beisl, Stefan (2019)
The present work addresses the synthesis of nanofiltration composite membranes with bactericide properties. The cellulose acetate based membranes with polyvinylpyrrolidone coated silver nano particles, silver ion-exchanged beta-zeolite and beta-zeolite are casted by the phase inversion technique and subjected to an annealing post-treatment. They are characterized in terms of the nanofiltration permeation performance and antibacterial properties. The incorporation of silver nanoparticles produces a threefold increase in the membrane hydraulic permeability when compared to the silver-free membranes and the incorporation of silver ion loaded zeolite resulted in a 56.3% increase in hydraulic permeability. In contrast to the influence of silver presence, either in nanometric or in the ionic form, the presence of zeolite does not significantly influence the hydraulic permeability. The rejection coefficients to salts range from 83% to 93% for the silver ion-exchanged zeolite membrane and from 84% to 97% for the polyvinylpyrrolidone coated silver nanoparticles membrane. They are higher for sulfate salts than for chloride salts. The antibacterial properties of the membranes were evaluated against Escherichia coli. The results have shown that the silver ion-exchanged beta-zeolite membrane was effective in inactivating Escherichia coli after just 210 min of contact time. No bacterial activity was detected following 24 h of contact time with the membrane containing polyvinylpyrrolidone coated silver nanoparticles. A reduction of more than 6-log, in the number of Escherichia coli, was achieved for both membranes. The different patterns of bactericide activity are associated to the silver speciation in metallic or ionic form. The high flux nanofiltration composite membranes with bactericidal properties represent a strong asset in water treatment biofouling control.